Effects of Vitamin C on the Gonad Growth, Texture Traits, Collagen Content and Synthesis Related Gene Expression of Sea Urchin (Mesocentrotus nudus) - Haijing Liu; Panke Gong; Dan Gou; Jiahao Cao; Weixiao Di; Jun Ding; Yaqing Chang; Rantao Zuo (Animals, 2024)
The market value of sea urchin gonads is determined by the specific characteristics associated with gonad size and texture. Formulated feeds can effectively promote the gonad growth of sea urchins but cannot assure essential gonad texture traits. The objective of this study was to investigate the impact of vitamin C (VC) on the gonad growth, texture, collagen content, and the expression of genes involved in the collagen synthesis of sea urchins (Mesocentrotus nudus). Graded amounts of VC (0, 3000 and 6000 mg/kg) were supplemented to make three formulated feeds. Fresh kelp (Saccharina japonica) was used as the control diet. Each diet was randomly distributed to three tanks of M. nudus. The results indicated that the gonadosomatic index (GSI) and texture traits of M. nudus fed C3000 were significantly greater than those fed C0 and C6000. Collagen type I (Col I) in the gonads of M. nudus fed C3000 showed significantly greater areas than those fed C0 and C6000. Consistently, the expression levels of collagen alpha-1 (colp1α) of M. nudus fed C3000 were significantly higher than those fed C0 and C6000. As for the transforming growth factor beta (tgf-β)/Smads pathway, the expression levels of collagen synthesis genes (tgf-β receptor 1 and 2, smad nuclear-interacting protein 1 (snip1) and prolyl 4-hydroxylase subunit beta (p4hβ)) in the C3000 group were significantly greater than those in the C0, C6000 and kelp groups. On the contrary, the expression levels of collagen degradation genes (lysyl oxidase-like 2 (loxl2) and matrix metalloproteinase 14 (mmp14)) in the C3000 group were significantly lower than those in the C0, C6000 and kelp groups. In conclusion, VC at an addition level of 3000 mg/kg significantly increased the gonad texture and collagen contents of M. nudus, which could be accomplished by increasing collagen synthesis and inhibiting collagen degradation through the tgf-β/Smads pathway. These results could contribute to better understanding the beneficial effects of VC addition on the gonad texture quality of M. nudus.